Support and FT synthesis catalyst, their preparation method and their application
Through a new preparation method, hollow oxidized microspheres similar to strawberries were prepared, which solved the problems of small size, difficulty in expansion, low efficiency and high cost in the prior art, and achieved more efficient catalyst support performance.
Patent Information
- Application Number
- JP2022525356
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-31
- Filing Date
- 2020-10-29
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2040-10-29
AI Technical Summary
The prior art has problems of small size, difficulty in expanding, low efficiency and high cost in preparing hollow microsphere oxidation materials, resulting in poor performance in catalyst support.
A new preparation method is adopted to prepare hollow oxidized microspheres similar to strawberries by mixing materials such as nitrates, dissolving agents and pore forming agents into colloidal paste, and molding and drying. The method includes molding and drying of the colloid paste, and forming oxidized microspheres with large pores and high surface area using high temperature infrared drying technology.
The prepared hollow oxidized microspheres have larger size and higher strength, suitable for catalyst support in fixed bed reactors, improving catalyst performance and efficiency, including improving CO conversion rate and C5+ hydrocarbide selectivity.
Smart Images

Figure 0007671750000005 
Figure 0007671750000006 
Figure 0007671750000007
Abstract
Description
Detailed Description of the Invention
[0001] [Technical field] The present disclosure relates to supported catalysts. In particular, the present disclosure relates to raspberry-like oxide microspheres, FT synthesis catalysts containing the oxide microspheres as supports, and their preparation methods and applications.
[0002] [Background technology] In the past few decades, there have been many literatures that have studied or reported hollow microspheres of inorganic materials. Compared with common solid spheres, hollow materials have low density and large specific surface area. They have been widely used, for example, as carriers for drugs and catalysts, and as adsorbents for gases. In recent years, the research and application of hollow microspheres of inorganic materials has attracted more and more attention.
[0003] Alumina hollow microspheres are a new type of high-temperature resistant thermal insulation material. They are prepared by smelting and spraying industrial alumina in an electric furnace, and have the crystal morphology of α-Al2O3. By using alumina hollow microspheres as the main body, articles of various shapes can be manufactured. The obtained articles can have mechanical strength several times higher than that of general lightweight products, and have a bulk density much smaller than that of solid products. They have been widely used in high-temperature and ultra-high-temperature furnaces, such as gasification furnaces in the petrochemical industry, reactors in the carbon black industry, and induction furnaces in the metallurgical industry. They have realized a very satisfactory effect on energy saving. At present, alumina hollow microsphere materials can be prepared by high-temperature melting and spray reaction, casting method, layer-by-layer (LbL) method, and microemulsion method.
[0004] Due to the advantages of good biocompatibility, easy availability, and low-cost raw materials, silica hollow microspheres have been widely used in the fields of drug carriers, biosignal markers, and coatings. The preparation of silica hollow microspheres has attracted extensive attention from researchers. The most widely proposed method involves using polystyrene microspheres as templates, coating the surface of the polystyrene microspheres with a silicon shell, and then removing the polystyrene core to obtain the silicon hollow microspheres. At present, the reported preparation methods mainly include: (1) electrostatic adsorption method; (2) modification with silicon-based crosslinkers; and (3) layer-by-layer method.
[0005] Zirconia hollow microspheres are plasma sprayed insulation materials used for surface modification of mechanical parts, such as aircraft engines, gas turbines, and heat treatment equipment. Coatings prepared from such microspheres have good thermal shock resistance and high temperature corrosion resistance. Therefore, when sprayed on high temperature parts such as aircraft engines, it can not only improve the mechanical performance of the engine, but also extend the life of the parts under high temperatures. Zirconia porous hollow microspheres are chemically stable, and can thereby be used as microcarriers for controlling the release of active substances (such as sustained release formulations of drugs). They do not react with the active ingredients of the loaded drugs, have good biocompatibility, and do not pollute the environment. In addition, they have nano-sized pores, which allows for effective control of particle size and pore diameter. Current methods for producing zirconia hollow microspheres include plasma spheronization and granulation by spray drying. Plasma spheronization is a method using a plasma spray gun as a heat source to heat treat porous agglomerated powder of zirconia prepared by other methods to obtain hollow microspheres.
[0006] Titania hollow microspheres can expand the specific surface area of titania, thereby providing more active sites for catalytic reactions. In addition, their higher crystallinity can reduce the rate of recombination of photogenerated electrons with active holes, thereby improving catalytic activity. In a further aspect, in terms of modification, the hollow structure can provide space for further modification of titania materials. There are many methods for synthesizing titania hollow microspheres, such as the template method, the flame burning method, the non-template method, etc. Among these, the template method is easy to control the pore size and shell thickness of the microspheres, and the dispersion is relatively uniform. However, the steps of the template method are complicated, and the shell of the microspheres is easily damaged during the removal of the template. The flame burning method and the non-template method have the advantages of continuous preparation process, simple operation, and no pollution. However, the prepared products are not uniform.
[0007] The Fischer-Tropsch synthesis process, also known as FT synthesis, is a process in which synthesis gas (a mixture of carbon monoxide and hydrogen) is used as a feedstock to synthesize liquid or hydrocarbons under suitable conditions in the presence of a catalyst. The synthesis process is a key step in the indirect conversion of non-petroleum resources such as coal, natural gas, and biomass into high-quality liquid fuels and chemical feedstocks.
[0008] In order to obtain an ideal distribution of FT synthesis products, one of the commonly used measures is to improve the FT synthesis catalyst, for example, by using hollow microspheres of inorganic materials as carriers. However, the current methods for preparing hollow microspheres of inorganic materials generally have the problem of being small-scale and not easy to expand. At the same time, some preparations may have low efficiency and high cost in raw materials. This substantially limits the use of microspheres as carriers in preparing catalysts. In addition, the prepared catalyst may not be able to meet the requirements on performance.
[0009] In fields such as petrochemistry, catalysts need to be strong, highly porous, and have low pressure drop to be suitable for use in fixed-bed reactors (microreactors, microchannel reactors, microchemical reactors, mesoscopic reactors, etc.) Thus, there is an increasing demand for high-strength, hollow microspheres of inorganic materials that can be used as supports.
[0010] Please note that the information disclosed in the above background is only used to facilitate the understanding of the present disclosure, and therefore may include information that does not constitute prior art known to those skilled in the art.
[0011] [Summary of the Disclosure] The present disclosure solves the problems of the prior art by providing raspberry-shaped oxide microspheres, FT synthesis catalysts containing the oxide microspheres as carriers, and their preparation methods and applications. The present disclosure provides oxide microspheres with hollow structure, good mass and heat transfer properties, and significantly improved strength. The oxide microspheres according to the present disclosure are particularly suitable for use as carriers for FT synthesis catalysts, and are particularly suitable for use in fixed-bed reactors such as microreactors, microchannel reactors, microchemical reactors, or mesoscopic reactors.
[0012] To achieve the above objectives, the present disclosure adopts the following technical solutions:
[0013] In one aspect, the present disclosure provides raspberry-shaped oxide microspheres, which are hollow microspheres having large pores on their surface, the hollow microspheres having a hollow structure therein, the large pores and the hollow structure being connected to form a cavity with an open end, and the oxide in the raspberry-shaped oxide microspheres is one or more selected from the group consisting of alumina, silica, zirconia, and titania.
[0014] In some embodiments, the raspberry-shaped oxide microspheres have a particle size of 3 to 2500 μm, preferably 10 to 500 μm.
[0015] In some embodiments, the hollow structure has a diameter of 1 to 2000 μm, preferably 1 to 400 μm.
[0016] In some embodiments, the large pores have a diameter of 0.2 to 1000 μm, preferably 0.5 to 200 μm.
[0017] In some embodiments, the shell of the hollow microsphere has a thickness of 0.2 to 1000 μm, preferably 0.5 to 200 μm.
[0018] In some embodiments, the raspberry-shaped oxide microspheres have a sphericity of 0.50 to 0.99.
[0019] In some embodiments, the raspberry-shaped oxide microspheres have a crushing rate of 0-1%.
[0020] In another aspect, the present disclosure provides a method for preparing the above-mentioned raspberry-shaped oxide microspheres, comprising the steps of: a step of sequentially adding a nitrate, a peptizer, a pore-forming agent, the oxide and / or a precursor thereof to a dispersant and stirring to obtain a dispersion slurry; Aging the dispersion slurry; and The aged dispersion slurry is sent to a drying device, and dried and shaped under conditions of an inlet gas temperature of 400 to 1200°C, preferably 450 to 700°C, and an outlet gas temperature of 50 to 300°C, preferably 120 to 200°C, to obtain raspberry-shaped oxide microspheres.
[0021] In some embodiments, the nitrate is one or more selected from the group consisting of aluminum nitrate, zirconium nitrate, lanthanum nitrate, and yttrium nitrate.
[0022] In some embodiments, the peptizer is one or more selected from the group consisting of an acid, a base, and a salt.
[0023] In some embodiments, the pore former is one or more selected from the group consisting of starch, synthetic cellulose, polymeric alcohol, and surfactants.
[0024] In some embodiments, the oxide and / or its precursor is one or more selected from the group consisting of an aluminum source, a silicon source, a zirconium source, and a titanium source, the aluminum source being one or more selected from the group consisting of pseudoboehmite, aluminum alkoxide, aluminum nitrate, aluminum sulfate, aluminum chloride, and sodium metaaluminate; the silicon source being one or more selected from the group consisting of silicate esters, sodium silicate, water glass, and silica sol; the zirconium source being one or more selected from the group consisting of zirconium dioxide, tetrahydrofuran, and the like. the titanium source is one or more selected from the group consisting of zirconium chloride, zirconyl chloride, zirconium hydroxide, zirconium sulfate, zirconium phosphate, zirconyl nitrate, zirconium nitrate, zirconium basic carbonate, and zirconium tetrabutoxide; the titanium source is one or more selected from the group consisting of titanium dioxide, metatitanic acid, titanium nitrate, titanyl sulfate, titanium dichloride, titanium trichloride, titanium tetrachloride, aluminum titanium chloride, tetraethyl titanate, tetrabutyl titanate, tetra-n-propyl titanate, and tetra-isopropyl titanate.
[0025] In some embodiments, the dispersant is one or more selected from the group consisting of water, an alcohol, a ketone, and an acid.
[0026] In some embodiments, the mass ratio of the nitrate, the peptizer, the pore-forming agent, and the oxide and / or its precursor is (10-500):(1-10):(10-500):(10-1000).
[0027] In some embodiments, a blasting agent may be added to the dispersant, the blasting agent being one or more selected from the group consisting of picric acid, trinitrotoluene, mercuric fulminate, nitroglycerin, nitrocellulose, Dana explosive, hexogen, lead azide, and C4 plastic explosive.
[0028] In some embodiments, the blasting agent is added in an amount of 0-1% of the total dry weight of the nitrate, the peptizer, the pore former, and the oxide and / or its precursor.
[0029] In some embodiments, the drying device is a flash drying device or a spray drying device.
[0030] In some embodiments, the aging is carried out at a temperature of 0 to 90°C, preferably 20 to 60°C.
[0031] In a further aspect, the present disclosure provides an FT synthesis catalyst comprising a support and an active metal component supported on the support, the active metal component being one or more selected from the group consisting of Co, Fe, and Ru, the support being a hollow microsphere having large holes on its surface, the hollow microsphere having a hollow structure inside, the large holes and the hollow structure being connected to form a cavity with an open end, and the oxide in the raspberry-shaped oxide microsphere being one or more selected from the group consisting of alumina and silica.
[0032] In some embodiments, the support is present in the catalyst in an amount of 25 to 95 wt %, preferably 30 to 90 wt %, on an oxide basis, and the active metal component is present in the catalyst in an amount of 5 to 75 wt %, preferably 10 to 70 wt %, on an oxide basis, based on the weight of the catalyst.
[0033] In some embodiments, the raspberry-shaped oxide microspheres have a particle size of 3-2500 μm, preferably 10-500 μm, and a sphericity of 0.50-0.99.
[0034] In some embodiments, the hollow structure has a diameter of 1 to 2000 μm, preferably 1 to 400 μm.
[0035] In some embodiments, the large pores have a diameter of 0.2 to 1000 μm, preferably 0.5 to 200 μm.
[0036] In some embodiments, the shell of the hollow microsphere has a thickness of 0.2 to 1000 μm, preferably 0.5 to 200 μm.
[0037] In some embodiments, the raspberry-shaped oxide microspheres have a crush rate of 0-1%.
[0038] In a further aspect, the present disclosure provides a method for preparing the above-mentioned FT synthesis catalyst, comprising the steps of: providing an impregnation solution of a compound containing raspberry-shaped oxide microspheres and the active metal component; Calcining the raspberry-shaped oxide microspheres to obtain a support; and A step of impregnating the carrier with the impregnation liquid, drying and activating the carrier by calcination to obtain an FT synthesis catalyst.
[0039] In some embodiments, the step of preparing the raspberry-shaped oxide microspheres may include the steps of: adding a nitrate, a peptizer, a pore former, an aluminum source and / or a silicon source to the dispersant and stirring to obtain a dispersed slurry; Aging the dispersion slurry; and The aged dispersion slurry is sent to a drying device, and dried and shaped under conditions of an inlet gas temperature of 400 to 1200°C, preferably 450 to 700°C, and an outlet gas temperature of 50 to 300°C, preferably 120 to 200°C, to obtain raspberry-shaped oxide microspheres.
[0040] In some embodiments, the nitrate is one or more selected from the group consisting of aluminum nitrate, zirconium nitrate, lanthanum nitrate, and yttrium nitrate.
[0041] In some embodiments, the peptizer is one or more selected from the group consisting of an acid, a base, and a salt.
[0042] In some embodiments, the pore former is one or more selected from the group consisting of starch, synthetic cellulose, polymeric alcohol, and surfactants.
[0043] In some embodiments, the aluminum source is one or more selected from the group consisting of pseudoboehmite, aluminum alkoxide, aluminum nitrate, aluminum sulfate, aluminum chloride, and sodium metaaluminate, and the silicon source is one or more selected from the group consisting of silicate ester, sodium silicate, water glass, and silica sol.
[0044] In some embodiments, the dispersant is one or more selected from the group consisting of water, an alcohol, a ketone, and an acid.
[0045] In some embodiments, the mass ratio of the nitrate, the peptizer, the pore-forming agent, and the oxide and / or its precursor is (10-500):(1-10):(10-500):(10-1000).
[0046] In some embodiments, a blasting agent may be added to the dispersant, the blasting agent being one or more selected from the group consisting of picric acid, trinitrotoluene, nitroglycerin, nitrocellulose, Dana explosive, hexogen, and C4 plastic explosive, the blasting agent being added in an amount of 0-1% of the total dry weight of the nitrate, the peptizer, the pore former, and the aluminum source and / or silicon source.
[0047] In some embodiments, the drying device is a flash drying device or a spray drying device.
[0048] In some embodiments, the aging is carried out at a temperature of 0 to 90°C, preferably 20 to 60°C.
[0049] In some embodiments, the calcination is carried out at a temperature of 400 to 1300°C, preferably 450 to 1100°C, and more preferably 500 to 700°C, the drying is carried out at a temperature of 80 to 200°C, preferably 100 to 150°C, and the activation by calcination is carried out at a temperature of 200 to 800°C, and preferably 300 to 600°C.
[0050] In a further aspect, the present disclosure provides a use of the above-described FT synthesis catalyst in a Fischer-Tropsch synthesis.
[0051] The method for preparing raspberry-shaped oxide microspheres with hollow structure according to the present disclosure has strong controllability, low cost and high efficiency, which is suitable for large-scale industrial application.
[0052] The raspberry-shaped oxide microspheres according to the present disclosure can be applied in various fields such as heat-resistant materials, biomaterials, photochemical materials, etc., all of which exhibit special advantages. Particularly in the field of catalysis, the oxide microspheres exhibit better mass and heat transfer properties, and have significantly higher strength than that of existing products with similar structure. When used in fixed-bed reactors (such as microreactors, microchannel reactors, microchemical reactors, or mesoscopic reactors), the oxide microspheres exhibit large porosity and small pressure loss, which allows them to be widely used in petrochemical and other fields.
[0053] Due to the hollow structure, the FT synthesis catalyst according to the present disclosure has a short diffusion distance and a large surface area, which can solve the diffusion problem in the FT synthesis reaction, improve the conversion rate of the FT synthesis and the selectivity to C5+ hydrocarbons, and reduce the selectivity to methane and CO2. Moreover, the selectivity to methane will not increase significantly due to the increase in temperature.
[0054] Description of the drawings 1 to 4 show SEM photographs of the raspberry-shaped oxide microspheres prepared in Preparation Examples 1 to 4.
[0055] FIG. 5 is a micrograph of the raspberry-shaped oxide microspheres prepared in Preparation Example 1.
[0056] FIG. 6 is a micrograph of the raspberry-shaped oxide microspheres prepared in Preparation Example 5.
[0057] FIG. 7 is a micrograph of the raspberry-shaped oxide microspheres prepared in Preparation Example 9.
[0058] FIG. 8 is a micrograph of the raspberry-shaped oxide microspheres prepared in Preparation Example 13. .
[0059] FIG. 9 is a micrograph of the oxide microspheres prepared in Comparative Preparation Example 1. FIG. 10 is a micrograph of the oxide microspheres prepared in Comparative Preparation Example 6.
[0060] FIG. 11 is a micrograph of the oxide microspheres prepared in Comparative Preparation Example 7.
[0061] FIG. 12 is a micrograph of the catalyst prepared in Procedure Example 1.
[0062] FIG. 13 is a micrograph of the catalyst prepared in Procedure Example 5.
[0063] FIG. 14 is a photomicrograph of the catalyst prepared in Comparative Example 1.
[0064] Detailed Description Hereinafter, the present application will be described in more detail with reference to the embodiments of the present application. It should be understood that the embodiments described herein are merely illustrative and not limiting.
[0065] In this disclosure, except for those explicitly described, any subject or subjects not described can be directly applied to those known in the art without any modification.Furthermore, any one of the embodiments described herein can be freely combined with one or more of the other embodiments described herein, and the resulting technical solutions or technical ideas should be considered as part of the original disclosure or original description of this disclosure, but should not be considered as new matters not disclosed or anticipated in this specification, unless it is obvious to a person skilled in the art that such combination is obviously unreasonable.
[0066] It should be noted that, unless it is obvious to a person skilled in the art that such combinations are obviously unreasonable, all of the features disclosed in this disclosure can be freely combined, and such combinations should be understood as being disclosed or recorded in this disclosure. It should be understood that the endpoints and any values in the ranges disclosed herein are not limited to the exact ranges or values, but include values close to those ranges or values. For numerical ranges, it is possible to combine between each endpoint of the numerical range, between each endpoint and each point of the numerical range, and between each point of the numerical range to give one or more new numerical ranges as if these numerical ranges were specifically disclosed herein. Except for the examples, all numerical values of parameters in this specification should be understood to be modified in all cases by the word "about", regardless of whether "about" actually appears before the numerical value.
[0067] According to one embodiment of the present disclosure, the present disclosure provides raspberry-shaped oxide microspheres, which are hollow microspheres having a raspberry-like structure, the hollow microspheres having large pores on their surfaces and hollow structures inside, the large pores and the hollow structures connecting to each other to form cavities with open ends, and the powder of the raspberry-shaped oxide microspheres has a crushing rate of 0-1%.
[0068] The oxide in the raspberry-shaped oxide microspheres may be an inorganic oxide, which may be one or more selected from the group consisting of alumina, silica, zirconia, magnesium oxide, calcium oxide and titania, preferably one or more selected from the group consisting of alumina, silica, zirconia and titania.
[0069] The raspberry-shaped oxide microspheres have a particle size of 3-2500 μm, preferably 10-500 μm, the hollow structure has a diameter of 1-2000 μm, preferably 1-400 μm, the large holes on the surface have a diameter of 0.2-1000 μm, preferably 0.5-200 μm, and the raspberry-shaped oxide microspheres have a shell layer surrounding the cavity, the thickness of which is 0.2-1000 μm, preferably 0.5-200 μm.
[0070] The raspberry-shaped oxide microspheres have a spherical appearance and their sphericity is 0.50-0.99.
[0071] The sphericity of the microspheres can be calculated according to the following formula: σ=4πA / L 2 where σ is the sphericity and A is the projected area of the microsphere (m 2 ), L is the projected perimeter of the microsphere (m), and A and L are obtained by processing the SEM photograph of the microsphere with the image processing software Image-Pro Plus.
[0072] The pulverization rate of the raspberry-like oxide microsphere powder according to the present disclosure is measured according to the method provided in the standard Q / SH3360 226-2010 for the same strength. In particular, this method includes the following: Select sieves S1 and S2 with mesh openings of M1 and M2 respectively (where M1 < M2), sieve the microsphere powder to be tested through sieve S1 with a mesh opening of M1, and further sieve the microsphere powder that has passed through sieve S1 through sieve S2 with a mesh opening of M2. Use the microsphere powder cut off by sieve S2 as the test sample; Add a certain amount of the test sample to a steel cylindrical container with a cross-sectional diameter of 10 mm, apply pressure with the cylinder to apply a certain pressure and a certain time load to the microsphere powder as the test sample, sieve the pressurized microsphere powder with sieve S2 with a mesh opening of M2, record the mass of the microsphere powder that has passed through sieve S2, and calculate the pulverization rate of the microsphere powder by dividing the mass of the microsphere powder that has passed through sieve S2 by the total mass of the added microsphere powder.
[0073] In the present disclosure, M1 is 100 mesh, M2 is 150 mesh, the pressure is 100 N, and the time is 10 seconds.
[0074] The pulverization rate can be used to evaluate the strength of the microspheres. The lower the pulverization rate, the higher the strength of the microspheres.
[0075] The raspberry-like oxide microsphere powder according to the present disclosure achieves a low pulverization rate under the above conditions. This indicates that it has significantly higher strength than currently known oxide microspheres such as the apple-like molecular sieve hollow microspheres disclosed in CN108404970A. This is due to the differences in the raw materials and preparation methods used. The raspberry-like oxide microspheres according to the present disclosure have greater porosity and higher strength. When used in a fixed bed reactor, the pressure loss can be significantly reduced, and it has excellent processability and wear resistance performance. The catalysts prepared using these as carriers have a short reaction diffusion distance and promising applications. They may also be made into high-temperature resistant thermal insulation materials, biomaterials, and photochemical materials.
[0076] According to a further aspect of the present disclosure, the present disclosure provides an FT synthesis catalyst comprising a support and an active metal component supported on the support. The active metal component is a Group VIII metal component, preferably one or more selected from the group consisting of Co, Fe and Ru. The active metal component may have activity in the order of Ru>Co>Fe, and may be capable of chain growth in the order of approximately Ru>Co≒Fe. The support may be the above-mentioned raspberry-shaped oxide microspheres, and the oxide in the raspberry-shaped oxide microspheres is one or more selected from the group consisting of alumina and silica.
[0077] In the FT synthesis catalyst according to the present disclosure, the support is present in an amount of 25 to 95 wt %, preferably 30 to 90 wt %, based on the weight of the catalyst, and the active metal component is present in an amount of 5 to 75 wt %, preferably 10 to 70 wt %, more preferably 12 to 30 wt %, based on the weight of the oxide.
[0078] The FT synthesis catalyst according to the present disclosure can be used in a fixed bed reactor, such as a microchannel reactor, for the Fischer-Tropsch synthesis reaction.
[0079] Raspberry-shaped oxide microspheres according to the present disclosure may be prepared by a method which may include the following steps: adding a nitrate, a peptizer, a pore former, and the oxide or a precursor thereof to the dispersant, and stirring to obtain a dispersion slurry; Aging the dispersion slurry; and The aged dispersion slurry is sent to a drying device, and dried and shaped under conditions of an inlet gas temperature of 400 to 1200°C, preferably 450 to 700°C, and an outlet gas temperature of 50 to 300°C, preferably 120 to 200°C, to obtain raspberry-shaped oxide microspheres.
[0080] In the method according to the present disclosure, the nitrate is one or more selected from the group consisting of aluminum nitrate, zirconium nitrate, lanthanum nitrate and yttrium nitrate. The nitrate ions in the nitrate can be utilized as an oxidizing agent for the pore former under high temperature conditions. They undergo self-propagating combustion reactions at high temperatures, explosively generating gases and steam, resulting in the formation of cavities in the oxide material.
[0081] In the above method according to the present disclosure, the peptizing agent is one or more selected from the group consisting of an acid, a base, and a salt. The acid can be selected from the group consisting of an inorganic acid (e.g., hydrochloric acid, sulfuric acid, nitric acid, etc.), an organic acid (formic acid, acetic acid, oxalic acid, etc.), and a combination of one or more inorganic or organic acids. The base can be selected from the group consisting of an inorganic base (sodium hydroxide, potassium hydroxide, barium hydroxide, calcium hydroxide, aluminum hydroxide, lithium hydroxide, magnesium hydroxide, zinc hydroxide, copper hydroxide, ferric hydroxide, lead hydroxide, cobalt hydroxide, chromium hydroxide, zirconium hydroxide, nickel hydroxide, ammonium hydroxide, soda ash (anhydrous sodium carbonate), sodium carbonate (monohydrate, heptahydrate, and decahydrate), sodium bicarbonate (baking soda), potassium carbonate, potassium bicarbonate, etc.), an organic base (amine compounds, alkali metal salts of alcohols, alkaloids, lithium alkyl metal compounds, etc.), and a combination of one or more inorganic or organic bases. The salts may be selected from the group consisting of salts of inorganic acids (such as hydrochlorides, sulfates, nitrates, etc.), salts of organic acids (such as formates, acetates, oxalates, etc.), and combinations of one or more of the salts of inorganic or organic acids.
[0082] In the method according to the present disclosure, the pore-forming agent is one or more selected from the group consisting of starch, synthetic cellulose, polymeric alcohol and surfactant. The synthetic cellulose is preferably one or more of carboxymethylcellulose, methylcellulose, ethylcellulose and hydroxycellulose fatty alcohol polyvinyl ether. The polymeric alcohol is preferably one or more of polyethylene glycol, polypropanol, polyvinyl alcohol and polypropylene alcohol (PPG). The surfactant is preferably one or more of fatty alcohol polyvinyl ether, fatty alcohol amide and its derivatives, acrylic acid copolymer and maleic acid copolymer having a molecular weight of 200 to 2,000,000.
[0083] In the method according to the present disclosure, the oxides and / or precursors thereof may be directly alumina, silica, zirconia and titania or may be precursors for forming these oxides. In particular, the oxides and / or precursors thereof may be one or more selected from the group consisting of an aluminum source, a silicon source, a zirconium source and a titanium source. The aluminum source is one or more selected from the group consisting of pseudoboehmite, aluminum alkoxide, aluminum nitrate, aluminum sulfate, aluminum chloride and sodium metaaluminate. The silicon source is one or more selected from the group consisting of silicate esters, sodium silicate, water glass and silica sol. The zirconium source is one or more selected from the group consisting of zirconium dioxide, zirconium tetrachloride, zirconyl chloride, zirconium hydroxide, zirconium sulfate, zirconium phosphate, zirconyl nitrate, zirconium nitrate, basic zirconium carbonate and zirconium tetrabutoxide. The titanium source is one or more selected from the group consisting of titanium dioxide, metatitanic acid, titanium nitrate, titanyl sulfate, titanium dichloride, titanium trichloride, titanium tetrachloride, aluminum titanium chloride, tetraethyl titanate, tetrabutyl titanate, tetra-n-propyl titanate, and tetraisopropyl titanate.
[0084] When using the above-mentioned aluminum source, silicon source, zirconium source and titanium source, the solution may further contain a chemical reagent for precipitating or gelling them, such as an acid (e.g., an inorganic acid such as hydrochloric acid, sulfuric acid, nitric acid, etc., or an organic acid such as acetic acid) and / or a base (sodium carbonate, sodium hydroxide, etc.).
[0085] When it is necessary to prepare an oxide composition containing other components, the oxides may further include vanadium oxide, chromium oxide, manganese oxide, molybdenum oxide, tungsten oxide, iron oxide, cobalt oxide, nickel oxide, copper oxide, etc. Precursors of these oxides can be used.
[0086] Said precursors of said oxides may be converted to the corresponding oxides under the conditions of the method according to the present disclosure.
[0087] In the method according to the present disclosure, the dispersant is one or more selected from the group consisting of water, alcohol, ketone and acid. The alcohol may be methanol, ethanol, propanol, etc. The ketone may be acetone, butanone, etc. The acid may be formic acid, acetic acid, propionic acid, etc. Preferably, the dispersant is a mixture of water and a small amount of ethanol. The small amount of ethanol may have a better dispersing effect in water, and may be used as a boiling point adjuster to adjust the dispersant so that the effect of evaporating water and the effect of shrinking droplets are more compatible. As a result, they make the appearance of the microspheres more uniform and smooth.
[0088] In the method according to the present disclosure, the mass ratio of the nitrate, the peptizer, the pore-forming agent, and the oxide and / or its precursor is (10-500):(1-10):(10-500):(10-1000).
[0089] In the method according to the present disclosure, the nitrate, the peptizer, the pore former, and the oxide and / or its precursor may be added to the dispersant sequentially or simultaneously. The order of addition may also be adjusted according to the solubility of each ingredient. While adding them, they may be stirred to mix them evenly.
[0090] The method according to the present disclosure may further include adding a blasting agent to the dispersion before or after the addition of the oxide. The blasting agent is one or more selected from the group consisting of picric acid, trinitrotoluene, nitroglycerin, nitrocellulose, Dana explosive, hexogen, and C4 plastic explosive. Prior to the drying and shaping, the blasting agent should be mixed uniformly with the other materials. The blasting agent is present in an amount of 0-1% of the total dry weight of the nitrate, the peptizer, the pore former, and the oxide and / or its precursor.
[0091] In the method according to the present disclosure, the nitrate, the deflocculating agent, the pore forming agent, and the oxide or its precursor are sequentially added to a dispersing agent to prepare a slurry. The slurry is uniformly stirred and then fed into a sand mill or colloid mill for grinding to obtain a dispersed slurry. During the preparation of the slurry, the slurry generally has a solid content of 5-60 wt %. The grinding time is 1-30 min. After the mixing and grinding, the particles of the aluminum source, silicon source, zirconium source, and titanium source in the slurry can be ground to an average particle size of 0.01-10 μm.
[0092] After the above mixing and grinding, the raw materials are completely dissolved and dispersed, and the dispersion slurry is made uniform. The grinding equipment used can be a colloid mill, a sand mill or other equipment. The selection criterion is to grind the catalyst powder to the required average particle size, i.e. less than 10 μm.
[0093] Thereafter, the above-mentioned dispersed slurry is aged at a temperature of 0 to 90° C. for 0.1 to 24 hours, preferably 0.5 to 2 hours.
[0094] After the aging, the dispersion slurry is sent to a drying device, and dried and shaped under normal pressure conditions with an inlet gas temperature of 400 to 1200°C, preferably 450 to 700°C, and an outlet gas temperature of 50 to 300°C, preferably 120 to 200°C, to obtain raspberry-shaped oxide microspheres.
[0095] The drying equipment used in this disclosure may be a flash drying equipment and a spray drying equipment, preferably a spray drying equipment. Flash drying and spray drying are common methods used to dry materials. The wet material is dispersed in a drying tower, and then contacted with hot air to rapidly evaporate the moisture to obtain a dry product. The spray drying method can directly dry aqueous solutions and emulsions into powdery or granular products, eliminating the need for procedures such as evaporation and grinding.
[0096] The working principle of spray drying is to disperse the material to be dried into very fine mist-like particles by mechanical action (pressure, centrifugal force, air flow atomization, etc.). This increases the surface area for water evaporation and accelerates the drying process. By contacting with hot air, most of the water is removed in a short time. As a result, the solids in the material are dried into powder.
[0097] The spray drying apparatus used in this disclosure may be a conventional apparatus of an existing process. In this disclosure, there is no special limitation on the spray drying apparatus. In general, the spray drying apparatus may include a feed system, a hot gas system, a drying tower system, a receiving system, and a sealing system. The feed system connects with the drying tower system at the center of the upper end, the hot gas system connects with the drying tower system at the side of the upper end, the receiving system connects with the drying tower system at the lower end, and the sealing system connects with the hot gas system. In general, the spray drying process may necessarily include three functions, namely, the atomization of the original liquid, the drying of the microdroplets during the spraying, and the separation and recovery of the fine powder product. The spray drying apparatus usually includes an atomizer, a drying chamber, and a fine powder recovery device corresponding to the above functions.
[0098] The spray drying process may involve many control parameters and complex factors. Therefore, the product after spray drying may have very complex particle sizes and particle shapes. In general, the product may have a particle size of the order of microns and may be a mixture of various shapes, including spherical, disk-shaped, apple-shaped, grape-shaped, hollow, half-moon-shaped, etc. In particular, it is difficult to selectively mold the product into an ideal single shape such as hollow.
[0099] One method in the prior art involves forming a spherical emulsion from a molecular sieve-containing dispersion by the surface tension of a surfactant, and then shaping the spherical emulsion by spraying at low temperature. During shaping by spraying, the pore-forming agent in the spherical emulsion can be vaporized or pyrolyzed. The gas produced by vaporization and pyrolysis can make the interior of the spherical emulsion hollow. The gradual release of the gas can form large pores on the surface, which are connected to the hollow structure inside. Also, during shaping by spraying, the molecular sieve particles can form secondary accumulated pores. The pores become mesopores on the surface of the molecular sieve microspheres. Combined with subsequent calcination, the hollow molecular sieve microspheres are obtained as large particles.
[0100] In the present disclosure, the shaping by drying is carried out at a high temperature of 400-1200°C inlet gas temperature. In this process, the nitrates and the pore-forming agents in the droplets undergo a strong oxidation-reduction reaction, resulting in self-propagating combustion and strong explosion. Thus, a large amount of gas is generated instantaneously. At the same time, when the droplets are sprayed into the high-temperature area, strong evaporation occurs on the surface. Due to the resulting surface tension, the droplets may contract rapidly. The combined effect of the strong internal explosion and strong external contraction leads to the formation of raspberry-shaped hollow materials with very high strength. Thus, the prepared raspberry-shaped oxide microspheres may have high strength, high sphericity, and high qualification rate of the product.
[0101] According to a further aspect of the present disclosure, the present disclosure provides raspberry-shaped oxide microspheres prepared by the method according to the present disclosure described above.
[0102] The raspberry-shaped oxide microspheres according to the present disclosure can be used as carriers after calcination. They can be prepared into various catalysts by loading corresponding active components. The calcination can be carried out at a temperature of 400-1300°C, preferably 450-1100°C, more preferably 500-700°C, for 1-12 hours, preferably 2-8 hours, more preferably 3-4 hours.
[0103] The support prepared from the raspberry-shaped oxide microspheres of the present disclosure has a specific surface area of about 0.1 to 900 m 2 / g, preferably 10 to 300m 2 / g, and the pore volume may be about 0.01 to 3.6 mL / g, preferably 0.1 to 0.9 mL / g.
[0104] Furthermore, the raspberry-like oxide microspheres according to the present disclosure can also be used as high-temperature resistant insulating materials, biomaterials, medicinal materials, or photochemical materials (eg, photocatalytic materials).
[0105] The FT synthesis catalyst according to the present disclosure can be prepared by a method that may include: providing raspberry shaped oxide microspheres; calcining the raspberry-shaped oxide microspheres to obtain a support; and A step of impregnating the support with an impregnation solution of a compound containing the active metal component, drying and activating the support by calcination to obtain an FT synthesis catalyst.
[0106] In the method according to the present disclosure, the step of providing raspberry-shaped oxide microspheres may include preparing raspberry-shaped oxide microspheres by the methods described above.
[0107] In the impregnation solution of the compound containing the active metal component, the compound containing the active metal component is one or more selected from the group consisting of soluble compounds (e.g., one or more of nitrates, acetates, basic carbonates, hydrochlorides, and soluble complexes containing the active metal component, preferably nitrates and / or basic carbonates). Taking cobalt as an example, the compound containing the active metal component is one or more selected from the group consisting of cobalt nitrate, cobalt acetate, cobalt bicarbonate, cobalt chloride, and soluble complexes of cobalt, preferably cobalt nitrate and / or cobalt bicarbonate.
[0108] The step of impregnating the carrier with an impregnation solution of a compound containing an active metal component may include the following steps: preparing an impregnation solution of a compound containing an active metal component, and then impregnating the carrier with the solution. The impregnation step can be carried out by a conventional method (such as excess liquid impregnation method, pore saturation impregnation method, etc.). By adjusting and controlling the concentration and amount of the impregnation solution of a compound containing an active metal component or the amount of the carrier, a catalyst having a specific content of active metal components can be prepared. This can be easily understood and achieved by those skilled in the art.
[0109] After impregnation, the impregnated product needs to be dried. The drying step can be carried out at a temperature of 80-200°C, preferably 100-150°C. The drying equipment and operating conditions used are those commonly used in existing drying techniques. There are no particular limitations on them in the present disclosure.
[0110] To obtain the catalyst, the dried product needs to be activated by calcination. The activation by calcination can be carried out at a temperature of 200-800°C, preferably 300-600°C. The apparatus and operating conditions used are those commonly used in the prior art related to calcination. There are no particular limitations on them in the present disclosure.
[0111] The use of raspberry-shaped oxide microspheres can reduce the waste of support and catalyst, thereby saving materials. At the same time, the shape efficiency factor can be improved due to the hollow structure, which can promote diffusion to improve reaction efficiency and selectivity to the target product. In reactions with relatively large thermal effects, the hollow support can also reduce the generation of hot spots, thereby having good inherent safety.
[0112] The use of raspberry-shaped oxide microspheres as the support can provide a short diffusion distance and a large surface area. Thus, the diffusion problem in the FT synthesis reaction can be solved. The FT synthesis catalyst according to the present disclosure has good FT synthesis performance. It can improve the conversion rate of FT synthesis and the selectivity to C5+ hydrocarbons, and reduce the selectivity to methane and CO2. Moreover, the selectivity to methane does not increase significantly with increasing temperature. Moreover, the method according to the present disclosure is low-cost and can be applied to large-scale industrial applications.
[0113] The present invention will be described in detail below using examples, but the scope of the present disclosure is not limited thereto.
[0114] [Example] Reagents, Equipment, and Tests Details of some of the raw materials used in the following preparative and procedural examples are listed below: Pseudo-boehmite powder (manufactured by Changling Catalyst Factory, solid content 69.5% by weight, γ-Al2O3 content 98% by weight or more); Aluminium sol (Zhoucun Catalyst Factory, Al2O3 content 22 wt%); Sodium silicate (manufactured by Jinan Huifengda Chemical Co., Ltd., coefficient 3.1-3.4, content of insoluble species less than 0.4%) Ammonia water, hydrochloric acid, nitric acid, sulfuric acid, aluminum sulfate, aluminum chloride, zirconium hydroxide, zirconyl chloride, titanium tetrachloride, titanium dioxide (China National Pharmaceutical Group Chemical Reagent Co., Ltd., industrial grade); Polyethylene glycol PEG4000 powder (from Wenzhou Shuangxiao Rubber and Plastic Material Co., Ltd.); methylcellulose (Hubei Jiangmin Taihua Chemical Co, Ltd.); Ethyl orthosilicate (TEOS, manufactured by Jinan Huate Chemical Co, Ltd., content about 99%); Aluminum nitrate, titanium nitrate, zirconium nitrate, yttrium nitrate, magnesium nitrate (Yutai Qixin Chemical Co., Ltd., industrial grade) Test Method: 1. The crushing rate of the support powder and catalyst powder was measured according to the following method: The microsphere powder to be tested was sieved through a 100 mesh sieve. The microsphere powder that passed through the sieve was further sieved through a 150 mesh sieve. The microsphere powder cut off by the 150 mesh sieve was used as the sample to be tested. A certain amount of microsphere powder (particle size 100-150 mesh) was added to a steel cylinder container with a cross-sectional diameter of 10 mm. The microsphere powder was pressed through the cylinder and a specific pressure (100 N) was applied for a specific time (10 seconds). The pressed microsphere powder was sieved through a 150 mesh sieve. The mass of the microsphere powder that passed through the sieve was recorded. The crushing rate of the microsphere powder was determined by dividing the mass of the microsphere powder that passed through the sieve by the total mass of the added microsphere powder.
[0115] 2. Pressure drop across the catalyst bed was measured using: A precision standard pressure gauge was attached to the inlet end of the bed. Here, the gas hourly space velocity was 24,000 h -1 The gas medium was nitrogen.
[0116] 3. The FT synthesis reaction performance of the catalyst was evaluated in a fixed-bed reactor.
[0117] Before using the FT synthesis catalyst, the catalyst was reduced to elemental metal. The conditions for reducing the catalyst are as follows: normal pressure, heating rate of 5°C / min, hydrogen space velocity of 600 h -1 After reduction, the reaction performance was tested under the following conditions: H2 / CO / N2=45% / 45% / 10% (volume ratio) feed gas composition, pressure 2.5 MPa, temperatures 200°C, 210°C, and 220°C, and space velocity of synthesis gas (feed gas) 24,000 h -1 The reaction was run at each reaction temperature for 12 hours, after which gas samples were taken for chromatographic analysis.
[0118] [Preparation Example 1] 20 kg of water was added to the reaction autoclave. To this, 1.2 kg of aluminum nitrate was added, followed by 200 g of concentrated nitric acid, then 2.3 kg of PEG4000, and finally 4 kg of pseudoboehmite powder. The mixture was stirred uniformly and ground to obtain a dispersed slurry.
[0119] The dispersed slurry was stirred and aged at 35° C. for 1.5 hours.
[0120] The aged dispersion slurry was sent to a spray dryer and dried to form raspberry-shaped oxide microspheres. The atomization pressure of the spray dryer was 0.3-3.0 MPa, the pressure inside the tower was -0.0010--0.0090 MPa, the inlet gas temperature at the start of drying was 580°C, and the outlet gas temperature at the end of drying was 160°C.
[0121] SEM images of the raspberry-shaped oxide microspheres are shown in Figure 1. Their micrographs are shown in Figure 5.
[0122] [Preparation Example 2] 20 kg of water was added to the reaction autoclave. To this, 0.5 kg of zirconium nitrate was added, followed by 175 g of concentrated nitric acid, then 2 kg of PEG4000 and 5 g of nitroglycerin, and finally 4.6 kg of pseudoboehmite powder. The mixture was stirred uniformly and ground to obtain a dispersed slurry.
[0123] The dispersed slurry was stirred and aged at 25° C. for 0.5 h.
[0124] The aged dispersion slurry was sent to a spray dryer and dried to form raspberry-shaped oxide microspheres. The atomization pressure of the spray dryer was 0.3-3.0 MPa, the tower pressure was -0.0010--0.0090 MPa, the inlet gas temperature was 560°C when drying started, and the outlet gas temperature was 140°C when drying ended.
[0125] An SEM photograph of the raspberry-shaped oxide microspheres is shown in FIG.
[0126] [Preparation Example 3] 30 kg of water was added to the reaction autoclave. To this, 1.2 kg of aluminum nitrate was added, followed by 200 g of concentrated nitric acid and 4.5 kg of sodium carbonate, then 2.3 kg of methyl cellulose and 10 g of picric acid, and finally 14 kg of aluminum sulfate. The mixture was stirred uniformly and ground to obtain a dispersed slurry.
[0127] The dispersed slurry was stirred and aged at 30° C. for 1 hour.
[0128] The aged dispersion slurry was sent to a spray dryer and dried to form raspberry-shaped oxide microspheres. The atomization pressure of the spray dryer was 0.3-3.0 MPa, the pressure inside the tower was -0.0010--0.0090 MPa, the inlet gas temperature at the start of drying was 580°C, and the outlet gas temperature at the end of drying was 130°C.
[0129] An SEM photograph of the raspberry-shaped oxide microspheres is shown in FIG.
[0130] [Preparation Example 4] 40 kg of water was added to the reaction autoclave. To this, 1.2 kg of yttrium nitrate was added, followed by 230 g of concentrated nitric acid and 4.8 kg of sodium carbonate, then 2.8 kg of methyl cellulose and 15 g of nitrocellulose, and finally 12.5 kg of aluminum chloride. The mixture was stirred uniformly and ground to obtain a dispersed slurry.
[0131] The dispersed slurry was stirred and aged at 30° C. for 1.5 hours.
[0132] The aged dispersion slurry was sent to a spray dryer and dried to form raspberry-shaped oxide microspheres. The atomization pressure of the spray dryer was 0.3-3.0 MPa, the pressure inside the tower was -0.0010--0.0090 MPa, the inlet gas temperature at the start of drying was 560°C, and the outlet gas temperature at the end of drying was 141°C.
[0133] An SEM photograph of the raspberry-shaped oxide microspheres is shown in FIG.
[0134] [Preparation Example 5] 40 kg of water was added to the reaction autoclave. To this, 1.2 kg of aluminum nitrate was added, followed by 200 g of concentrated nitric acid, then 2 kg of PEG4000 and 2 g of nitrocellulose, and finally 5.5 kg of sodium silicate. The mixture was stirred uniformly and ground to obtain a dispersed slurry.
[0135] The dispersed slurry was stirred and aged at 25° C. for 1.5 hours.
[0136] The aged dispersion slurry was sent to a spray dryer and dried to form raspberry-shaped oxide microspheres. The atomization pressure of the spray dryer was 0.3-3.0 MPa, the pressure inside the tower was -0.0010--0.0090 MPa, the inlet gas temperature at the start of drying was 560°C, and the outlet gas temperature at the end of drying was 120°C.
[0137] A micrograph of the raspberry-shaped oxide microspheres is shown in FIG.
[0138] [Preparation Example 6] 40 kg of water was added to the reaction autoclave. To this, 0.5 kg of aluminum nitrate was added, followed by 200 g of concentrated sulfuric acid, then 1 kg of PEG4000 and 5 g of picric acid, and finally 3 kg of sodium silicate. The mixture was stirred uniformly and ground to obtain a dispersed slurry.
[0139] The dispersed slurry was stirred and aged at 25° C. for 1 hour.
[0140] The aged dispersion slurry was sent to a spray dryer, where it was dried and molded to obtain raspberry-shaped oxide microspheres. Here, the atomization pressure of the spray dryer was 0.3-3.0 MPa, the pressure inside the tower was -0.0010--0.0090 MPa, the inlet gas temperature at the start of drying was 600°C, and the outlet gas temperature at the end of drying was 180°C.
[0141] [Preparation Example 7] 20L of water and ethanol solution (containing water and ethanol in a volume ratio of 3:1) was added to the reaction autoclave. To this, 1.2kg of aluminum nitrate was added, followed by 7L of concentrated ammonia water, then 2kg of ethyl cellulose and 7g of nitroglycerin, and finally 5kg of TEOS. The mixture was stirred uniformly and ground to obtain a dispersed slurry.
[0142] The dispersed slurry was stirred and aged at 25° C. for 1.5 hours.
[0143] The aged dispersion slurry was sent to a spray dryer, where it was dried and molded to obtain raspberry-shaped oxide microspheres. Here, the atomization pressure of the spray dryer was 0.3-3.0 MPa, the pressure inside the tower was -0.0010--0.0090 MPa, the inlet gas temperature at the start of drying was 700°C, and the outlet gas temperature at the end of drying was 160°C.
[0144] [Preparation Example 8] 20L of water and ethanol solution (containing water and ethanol in a volume ratio of 4:1) was added to the reaction autoclave. To this, 0.3kg of zirconium nitrate was added, followed by 3L of concentrated ammonia water, then 0.5kg of PEG4000 and 6g of picric acid, and finally 2.6kg of TEOS. The mixture was stirred uniformly and ground to obtain a dispersed slurry.
[0145] The dispersed slurry was stirred and aged at 25° C. for 1 hour.
[0146] The aged dispersion slurry was sent to a spray dryer and dried to form raspberry-shaped oxide microspheres. The atomization pressure of the spray dryer was 0.3-3.0 MPa, the pressure inside the tower was -0.0010--0.0090 MPa, the inlet gas temperature at the start of drying was 660°C, and the outlet gas temperature at the end of drying was 140°C.
[0147] [Preparation Example 9] 30 kg of water was added to the reaction autoclave. To this, 1.2 kg of zirconium nitrate was added, followed by 2.5 kg of PEG4000, and finally 7 kg of zirconium hydroxide. The mixture was stirred uniformly and ground to obtain a dispersed slurry.
[0148] The dispersed slurry was stirred and aged at 45° C. for 1.5 hours.
[0149] The aged dispersion slurry was sent to a spray dryer and dried to form raspberry-shaped oxide microspheres. The atomization pressure of the spray dryer was 0.3-3.0 MPa, the tower pressure was -0.0010--0.0090 MPa, the inlet gas temperature was 560°C when drying started, and the outlet gas temperature was 110°C when drying ended.
[0150] A micrograph of the raspberry-shaped oxide microspheres is shown in FIG.
[0151] [Preparation Example 10] 30 kg of water was added to the reaction autoclave. To this, 0.7 kg of zirconium nitrate was added, followed by 2 L of concentrated ammonia water, then 1.5 kg of PEG4000 and 8 g of picric acid, and finally 7 kg of zirconium hydroxide. The mixture was stirred uniformly and ground to obtain a dispersed slurry.
[0152] The dispersed slurry was stirred and aged at 25° C. for 2 hours.
[0153] The aged dispersion slurry was sent to a spray dryer and dried to form raspberry-shaped oxide microspheres. The atomization pressure of the spray dryer was 0.3-3.0 MPa, the tower pressure was -0.0010--0.0090 MPa, the inlet gas temperature was 560°C when drying started, and the outlet gas temperature was 140°C when drying ended.
[0154] [Preparation Example 11] 30 kg of water was added to the reaction autoclave. To this, 1.2 kg of aluminum nitrate was added, followed by 2 L of concentrated ammonia water, then 2 kg of PEG4000 and 2 g of trinitrotoluene, and finally 7 kg of zirconium hydroxide. The mixture was stirred uniformly and ground to obtain a dispersed slurry.
[0155] The dispersed slurry was stirred and aged at 25° C. for 1 hour.
[0156] The aged dispersion slurry was sent to a spray dryer and dried to form raspberry-shaped oxide microspheres. The atomization pressure of the spray dryer was 0.3-3.0 MPa, the pressure inside the tower was -0.0010--0.0090 MPa, the inlet gas temperature at the start of drying was 620°C, and the outlet gas temperature at the end of drying was 141°C.
[0157] [Preparation Example 12] 30 kg of water was added to the reaction autoclave. To this, 0.5 kg of magnesium nitrate was added, followed by 2.5 L of concentrated ammonia water, then 1 kg of methyl cellulose and 6 g of nitroglycerin, and finally 7.5 kg of zirconium hydroxide. The mixture was stirred uniformly and ground to obtain a dispersed slurry.
[0158] The dispersed slurry was stirred and aged at 25° C. for 1 hour.
[0159] The aged dispersion slurry was sent to a spray dryer and dried to form raspberry-shaped oxide microspheres. The atomization pressure of the spray dryer was 0.3-3.0 MPa, the tower pressure was -0.0010--0.0090 MPa, the inlet gas temperature was 560°C when drying started, and the outlet gas temperature was 140°C when drying ended.
[0160] [Preparation Example 13] 30 kg of water was added to the reaction autoclave. To this, 1.2 kg of titanium nitrate was added, followed by 2.5 kg of PEG4000 and 3 g of nitrocellulose, and finally 500 g of concentrated nitric acid and 6 kg of titanium dioxide. The mixture was stirred uniformly and ground to obtain a dispersed slurry.
[0161] The dispersed slurry was stirred and aged at 55° C. for 1.5 hours.
[0162] The aged dispersion slurry was sent to a spray dryer and dried to form raspberry-shaped oxide microspheres. The atomization pressure of the spray dryer was 0.3-3.0 MPa, the pressure inside the tower was -0.0010--0.0090 MPa, the inlet gas temperature at the start of drying was 480°C, and the outlet gas temperature at the end of drying was 120°C.
[0163] A micrograph of the raspberry-shaped oxide microspheres is shown in FIG.
[0164] [Preparation Example 14] 30 kg of water was added to the reaction autoclave. To this, 0.7 kg of titanium nitrate was added, followed by 2.6 L of concentrated ammonia water, then 1.5 kg of PEG4000 and 6 g of picric acid, and finally 500 g of concentrated nitric acid and 7 kg of titanium nitrate. The mixture was stirred uniformly and ground to obtain a dispersed slurry.
[0165] The dispersed slurry was stirred and aged at 25° C. for 2 hours.
[0166] The aged dispersion slurry was sent to a spray dryer and dried to form raspberry-shaped oxide microspheres. The atomization pressure of the spray dryer was 0.3-3.0 MPa, the pressure inside the tower was -0.0010--0.0090 MPa, the inlet gas temperature at the start of drying was 560°C, and the outlet gas temperature at the end of drying was 141°C.
[0167] [Preparation Example 15] 30 kg of water was added to the reaction autoclave. To this, 1.2 kg of aluminum nitrate was added, then 2.1 L of concentrated ammonia water, then 2 kg of PEG4000 and 2 g of trinitrotoluene, and finally 400 g of concentrated nitric acid and 7 kg of titanium tetrachloride were added. The mixture was stirred uniformly and ground to obtain a dispersed slurry.
[0168] The dispersed slurry was stirred and aged at 25° C. for 1.5 hours.
[0169] The aged dispersion slurry was sent to a spray dryer and dried to form raspberry-shaped oxide microspheres. The atomization pressure of the spray dryer was 0.3-3.0 MPa, the pressure inside the tower was -0.0010--0.0090 MPa, the inlet gas temperature at the start of drying was 620°C, and the outlet gas temperature at the end of drying was 150°C.
[0170] [Preparation Example 16] 30 kg of water was added to the reaction autoclave. To this, 0.5 kg of magnesium nitrate was added, followed by 2.4 L of concentrated ammonia water, then 1 kg of methyl cellulose and 6 g of nitroglycerin, and finally 400 g of concentrated nitric acid and 7 kg of titanium tetrachloride. The mixture was stirred uniformly and ground to obtain a dispersed slurry.
[0171] The dispersed slurry was stirred and aged at 25° C. for 1 hour.
[0172] The aged dispersion slurry was sent to a spray dryer and dried to form raspberry-shaped oxide microspheres. The atomization pressure of the spray dryer was 0.3-3.0 MPa, the tower pressure was -0.0010--0.0090 MPa, the inlet gas temperature was 560°C when drying started, and the outlet gas temperature was 140°C when drying ended.
[0173] Comparative Preparation Example 1 20 kg of water was added to the reaction autoclave. 4.5 kg of pseudoboehmite powder was added to this. The mixture was stirred uniformly. 200 g of concentrated hydrochloric acid was added to this. The mixture was pulverized. 2.3 kg of PEG4000 was added to this. The mixture was made into a slurry. The slurry was stirred and aged at 25°C for 1 hour. The mixture was dried and molded in a spray drying apparatus to obtain oxide microspheres. Here, the atomization pressure of the spray drying was 0.3 to 3.0 MPa, the pressure inside the tower was -0.0010 to -0.0090 MPa, the inlet gas temperature at the start of drying was 560°C, and the outlet gas temperature at the end of drying was 145°C.
[0174] A micrograph of the obtained oxide microspheres is shown in Figure 9. As can be seen from the figure, the microspheres were substantially solid, and the central portions thereof contained almost no hollow structure connected to the outside.
[0175] Comparative Preparation Example 2 30 kg of water was added to the reaction autoclave. To this, 5.5 kg of sodium silicate was added. The mixture was stirred uniformly. To this, 200 g of concentrated hydrochloric acid was added. The resulting dispersion was filtered. The precipitate was washed twice with ethanol and deionized water, respectively, to remove unreacted inorganic and organic impurities.
[0176] To this, 20 kg of water and 2.0 kg of PEG4000 were added. The mixture was made into a slurry. The slurry was stirred and aged at 25°C for 1 hour. The mixture was dried and molded in a spray dryer to obtain oxide microspheres. Here, the atomization pressure of the spray dryer was 0.3 to 3.0 MPa, the pressure inside the tower was -0.0010 to -0.0090 MPa, the inlet gas temperature at the start of drying was 450°C, and the outlet gas temperature at the end of drying was 120°C.
[0177] When observed under a microscope, the product had a structure similar to that of Comparative Preparation Example 1. That is, it was substantially solid, and its center portion contained almost no hollow structure connected to the outside.
[0178] Comparative Preparation Example 3 30 kg of water was added to the reaction autoclave. To this, 7 kg of zirconium hydroxide was added. The mixture was vigorously stirred at 30° C. until the materials were thoroughly mixed. The dispersion was ground in a grinder for 30 minutes.
[0179] After mixing and grinding, concentrated aqueous ammonia was added as an adjuster until the pH value reached approximately 10. After reacting for 2 hours, a dispersion was obtained. The dispersion was stirred and aged at 25°C for 1 hour. The mixture was dried and molded in a spray dryer to obtain oxide microspheres. Here, the atomization pressure of the spray dryer was 0.3 to 3.0 MPa, the pressure inside the tower was -0.0010 to -0.0090 MPa, the inlet gas temperature at the start of drying was 650°C, and the outlet gas temperature at the end of drying was 150°C.
[0180] When observed under a microscope, the product had a structure similar to that of Comparative Preparation Example 1. That is, it was substantially solid, and its center portion contained almost no hollow structure connected to the outside.
[0181] Comparative Preparation Example 4 30 kg of water was added to the reaction autoclave. To this, 6 kg of titanium dioxide and 500 g of concentrated hydrochloric acid were added. The mixture was vigorously stirred at 30° C. until the materials were thoroughly mixed. The resulting dispersion was ground in a grinder for 30 minutes.
[0182] After mixing, reaction, and grinding, concentrated ammonia water was added as an adjuster until the pH value reached about 9. After reacting for 2 hours, 2.5 kg of PEG4000 was added to obtain a dispersion. The dispersion was stirred and aged at 45°C for 1 hour. The mixture was dried and molded in a spray dryer to obtain oxide microspheres. Here, the atomization pressure of the spray dryer was 0.3 to 3.0 MPa, the pressure inside the tower was -0.0010 to -0.0090 MPa, the inlet gas temperature at the start of drying was 520°C, and the outlet gas temperature at the end of drying was 170°C.
[0183] When observed under a microscope, the product had a structure similar to that of Comparative Preparation Example 1. That is, it was substantially solid, and its center portion contained almost no hollow structure connected to the outside.
[0184] Comparative Preparation Example 5 5.5 kg of HZSM-5 molecular sieves (crystal size 300-350 nm), 3 kg of kaolin, 1 kg of cement, and 0.5 kg of ammonium carbonate were added to 20 kg of deionized water. The mixture was sheared and emulsified at 2000 rpm for 2 hours using a homogeneous emulsifier to form a homogeneous colloidal slurry with a solid content of 31.7%.
[0185] 300 g of P123 surfactant was added to the colloidal slurry, which was stirred for an additional hour to obtain a microsphere slurry.
[0186] The microsphere slurry was sent to a spray dryer, where the atomization pressure of the spray dryer was 2.8 MPa, the inlet temperature of the spray dryer was 280°C, and the outlet temperature was 120°C. After 2 to 5 seconds, the slurry was discharged from the outlet of the spray dryer to obtain microspheres.
[0187] Comparative Preparation Example 6 5.5 kg of HZSM-5 molecular sieves (crystal size 300-350 nm), 3 kg of kaolin, 1 kg of cement, and 0.5 kg of ammonium carbonate were added to 20 kg of deionized water. The mixture was sheared and emulsified at 2000 rpm for 2 hours using a homogeneous emulsifier to form a homogeneous colloidal slurry with a solid content of 31.7%.
[0188] 300 g of P123 surfactant was added to the colloidal slurry, which was stirred for an additional hour to obtain a microsphere slurry.
[0189] The microsphere slurry was sent to a spray dryer, where the atomization pressure of the spray dryer was 2.8 MPa, the inlet temperature of the spray dryer was 560°C, and the outlet temperature was 140°C. After 2 to 5 seconds, the slurry was discharged from the outlet of the spray dryer to obtain microspheres.
[0190] A micrograph of the obtained microspheres is shown in Figure 10. As can be seen from the figure, most of the microspheres had irregular shapes. Furthermore, the central portions of the microspheres hardly contained any hollow structure connected to the outside.
[0191] Comparative Preparation Example 7 5.5 kg of pseudoboehmite powder, 3 kg of kaolin, 1 kg of cement and 0.5 kg of ammonium carbonate were added to 20 kg of deionized water. The mixture was sheared and emulsified at 2000 rpm for 2 hours using a homogeneous emulsifier to form a homogeneous colloidal slurry with a solid content of 31.7%.
[0192] 300 g of P123 surfactant was added to the colloidal slurry, which was stirred for an additional hour to obtain a microsphere slurry.
[0193] The microsphere slurry was sent to a spray dryer, where the atomization pressure of the spray dryer was 2.8 MPa, the inlet temperature of the spray dryer was 280°C, and the outlet temperature was 120°C. After 2 to 5 seconds, the slurry was discharged from the outlet of the spray dryer to obtain microspheres.
[0194] A micrograph of the obtained microspheres is shown in Figure 11. As can be seen from the figure, the microspheres were substantially solid, and the central portions thereof contained almost no hollow structure connected to the outside.
[0195] [Operation Example] The following procedural examples were used to test the effect of using the oxide microspheres obtained in the Preparative Examples and Comparative Preparative Examples as supports on catalytic performance.
[0196] [Operation Example 1] The raspberry-shaped oxide microspheres obtained in Preparation Example 1 were calcined at 600° C. to obtain the support ZT1, whose physical properties are shown in Table 1.
[0197] The carrier ZT1 was impregnated with a cobalt nitrate solution to prepare a catalyst with a cobalt content of 16.0%. It was dried at a temperature of 120°C and calcined at 420°C to obtain the catalyst CAT1. Its physical properties are shown in Table 2.
[0198] A micrograph of the microspheres of catalyst CAT1 is shown in FIG.
[0199] [Operation Example 2] The raspberry-shaped oxide microspheres obtained in Preparation Example 2 were calcined at 500° C. to obtain the support ZT2, whose physical properties are shown in Table 1.
[0200] The carrier ZT2 was impregnated with a cobalt nitrate solution to prepare a catalyst with a cobalt content of 16.0%. It was dried at a temperature of 110°C and calcined at 350°C to obtain the catalyst CAT2. Its physical properties are shown in Table 2.
[0201] [Operation Example 3] The raspberry-shaped oxide microspheres obtained in Preparation Example 3 were calcined at 500° C. to obtain the support ZT3, whose physical properties are shown in Table 1.
[0202] The support ZT3 was impregnated with ferric nitrate solution to prepare a catalyst with an iron content of 15.0%. It was dried at 120°C and calcined at 420°C to obtain catalyst CAT3. Its physical properties are shown in Table 2.
[0203] [Operation Example 4] The raspberry-shaped oxide microspheres obtained in Preparation Example 4 were calcined at 700° C. to obtain the support ZT4, whose physical properties are shown in Table 1.
[0204] The support ZT4 was impregnated with ferric nitrate solution to prepare a catalyst with an iron content of 15.0%. It was dried at a temperature of 130°C and calcined at 370°C to obtain catalyst CAT4. Its physical properties are shown in Table 2.
[0205] [Operation Example 5] The support ZT3 was impregnated with ruthenium nitrosyl nitrate solution to prepare a catalyst with a ruthenium content of 3.0%. It was dried at 120°C and calcined at 420°C to obtain catalyst CAT5. Its physical properties are shown in Table 2.
[0206] A micrograph of the catalyst CAT5 microspheres is shown in FIG.
[0207] [Operation Example 6] The support ZT4 was impregnated with ruthenium nitrosyl nitrate solution to prepare a catalyst with a ruthenium content of 3.0%. It was dried at a temperature of 130°C and calcined at 380°C to obtain catalyst CAT6. Its physical properties are shown in Table 2.
[0208] [Operation Example 7] The raspberry-shaped oxide microspheres obtained in Preparation Example 5 were calcined at 600° C. to obtain the support ZT5, whose physical properties are shown in Table 1.
[0209] The carrier ZT5 was impregnated with a cobalt nitrate solution to prepare a catalyst with a cobalt content of 16.0%. It was dried at a temperature of 120°C and calcined at 420°C to obtain the catalyst CAT7. Its physical properties are shown in Table 2.
[0210] [Operation Example 8] The raspberry-shaped oxide microspheres obtained in Preparation Example 6 were calcined at 500° C. to obtain the support ZT6, whose physical properties are shown in Table 1.
[0211] The carrier ZT6 was impregnated with a cobalt nitrate solution to prepare a catalyst with a cobalt content of 16.0%. It was dried at a temperature of 110°C and calcined at 350°C to obtain the catalyst CAT8. Its physical properties are shown in Table 2.
[0212] [Operation Example 9] The raspberry-shaped oxide microspheres obtained in Preparation Example 7 were calcined at 500° C. to obtain the support ZT7, whose physical properties are shown in Table 1.
[0213] The support ZT7 was impregnated with ferric nitrate solution to prepare a catalyst with an iron content of 15.0%. It was dried at a temperature of 120°C and calcined at 420°C to obtain catalyst CAT9. Its physical properties are shown in Table 2.
[0214] [Operation Example 10] The raspberry-shaped oxide microspheres obtained in Preparation Example 8 were calcined at 700° C. to obtain the support ZT8, whose physical properties are shown in Table 1.
[0215] The catalyst with an iron content of 15.0% was prepared by impregnating the support ZT8 with ferric nitrate solution. It was dried at a temperature of 130°C and calcined at 370°C to obtain the catalyst CAT10. Its physical properties are shown in Table 2.
[0216] [Operation Example 11] The support ZT7 was impregnated with ruthenium nitrosyl nitrate solution to prepare a catalyst with a ruthenium content of 3.0%. It was dried at 120°C and calcined at 420°C to obtain catalyst CAT11. Its physical properties are shown in Table 2.
[0217] [Operation Example 12] The support ZT8 was impregnated with ruthenium nitrosyl nitrate solution to prepare a catalyst with a ruthenium content of 3.0%. It was dried at a temperature of 130°C and calcined at 380°C to obtain catalyst CAT12. Its physical properties are shown in Table 2.
[0218] [Operation Example 13] The oxide microspheres obtained in Preparation Example 9 were calcined at 600° C. for 3 hours to obtain the support ZT13, whose physical properties are shown in Table 1.
[0219] [Operation Example 14] The oxide microspheres obtained in Preparation Example 13 were calcined at 600° C. for 3 hours to obtain the support ZT14, whose physical properties are shown in Table 1.
[0220] [Comparative Operation Example 1] The oxide microspheres obtained in Comparative Preparation Example 1 were calcined at 600° C. for 3 hours to obtain a carrier DBZT1, the physical properties of which are shown in Table 1.
[0221] The carrier DBZT1 was impregnated with cobalt nitrate solution to prepare a catalyst with a cobalt content of 16.0%. It was dried at a temperature of 120°C and calcined at 420°C to obtain catalyst DBCAT-Co-1. Its physical properties are shown in Table 2. A micrograph of the microspheres of catalyst DBCAT-Co-1 is shown in Figure 15.
[0222] The carrier DBZT1 was impregnated with ferric nitrate solution to prepare a catalyst with an iron content of 15.0%. It was dried at a temperature of 120°C and calcined at 420°C to obtain catalyst DBCAT-Fe-1. Its physical properties are shown in Table 2.
[0223] The DBZT1 carrier was impregnated with a ruthenium nitrosyl nitrate solution to prepare a catalyst with a ruthenium content of 3.0%. It was dried at 120°C and calcined at 420°C to obtain the catalyst DBCAT-Ru-1. Its physical properties are shown in Table 2.
[0224] [Comparative Operation Example 2] The oxide microspheres obtained in Comparative Preparation Example 2 were calcined at 600° C. for 3 hours to obtain the carrier DBZT2, whose physical properties are shown in Table 1.
[0225] The carrier DBZT2 was impregnated with cobalt nitrate solution to prepare a catalyst with a cobalt content of 16.0%. It was dried at 120°C and calcined at 420°C to obtain catalyst DBCAT-Co-2. Its physical properties are shown in Table 2.
[0226] The DBZT2 carrier was impregnated with ferric nitrate solution to prepare a catalyst with an iron content of 15.0%. It was dried at 120°C and calcined at 420°C to obtain the DBCAT-Fe-2 catalyst. Its physical properties are shown in Table 2.
[0227] The DBZT2 carrier was impregnated with a ruthenium nitrosyl nitrate solution to prepare a catalyst with a ruthenium content of 3.0%, which was then dried at 120°C and calcined at 420°C to obtain the catalyst DBCAT-Ru-2. Its physical properties are shown in Table 2.
[0228] [Comparative Operation Example 3] The oxide microspheres obtained in Comparative Preparation Example 3 were calcined at 600° C. for 3 hours to obtain a carrier DBZT3, the physical properties of which are shown in Table 1.
[0229] [Comparative Operation Example 4] The oxide microspheres obtained in Comparative Preparation Example 4 were calcined at 600° C. for 3 hours to obtain the carrier DBZT4, whose physical properties are shown in Table 1.
[0230] [Comparative Operation Example 5] The oxide microspheres obtained in Comparative Preparation Example 5 were calcined at 600° C. for 3 hours to obtain the carrier DBZT5, whose physical properties are shown in Table 1.
[0231] [Table 1]
[0232] As can be seen from Table 1, the raspberry-shaped oxide microspheres obtained in the Preparation Examples according to the present invention had the same specific surface area, pore volume, and average pore size as the oxide microspheres obtained in the Comparative Preparation Examples when used as carriers. However, the oxide microspheres obtained in the Preparation Examples achieved substantial improvements in sphericity and strength. The oxide microspheres obtained in the Preparation Examples were significantly better than the sphericity and strength of the oxide microspheres obtained in the Comparative Preparation Examples.
[0233] [Table 2]
[0234] The catalysts of Operational Examples 1 to 12 and Comparative Operational Examples 1 to 2 were evaluated in relation to the FT synthesis reaction performance in a fixed bed reactor as described above. Before using the FT synthesis catalyst, the catalyst was reduced to elemental metal. The catalyst reduction conditions were normal pressure, heating rate of 5°C / min, hydrogen space velocity of 600 h -1 The temperature was 400°C for 5 hours.
[0235] After reduction, the reaction performance was tested under the following conditions:
[0236] The reaction conditions for the cobalt catalyst were: H2 / CO / N2 = 45% / 45% / 10% (volume ratio), pressure 2.5 MPa, temperatures 200°C, 210°C, and 220°C, and the space velocity of the synthesis gas (raw material gas) was 24,000 h -1 Each reaction temperature was operated and reacted for 12 hours. Then, gas samples were taken for chromatographic analysis. The main indicators of reaction performance included: CO conversion, selectivity to methane, and selectivity to C5+ hydrocarbons.
[0237] The reaction conditions for the iron-based catalyst are as follows: H2 / CO / N2 = 45% / 45% / 10% (volume ratio), pressure 2.5 MPa, temperatures 260°C, 270°C, and 280°C, and the space velocity of the synthesis gas (raw gas) is 15,000 h -1 Each reaction temperature was operated and reacted for 12 hours. Then, gas samples were taken for chromatographic analysis. The main indicators of reaction performance included: conversion of CO, selectivity to methane, selectivity to C5+ hydrocarbons, and selectivity to CO2.
[0238] The reaction conditions for the ruthenium catalyst are as follows: H2 / CO / N2 = 45% / 45% / 10% (volume ratio) feed gas composition, pressure 2.5 MPa, temperatures 200°C, 210°C, and 220°C, and space velocity of the synthesis gas (feed gas) 15,000 h -1Each reaction temperature was operated and reacted for 12 hours. Then, gas samples were taken for chromatographic analysis. The main indicators of reaction performance included: CO conversion, selectivity to methane, and selectivity to C5+ hydrocarbons.
[0239] The reaction performance test results are shown in Table 3.
[0240] [Table 3]
[0241] JPEG0007671750000004.jpg182169
[0242] The test results in Table 3 show that the Fischer-Tropsch synthesis catalyst prepared using the raspberry-like oxide microspheres according to the present disclosure as a support has better performance in FT synthesis under the same conditions. That is, the Fischer-Tropsch synthesis catalyst achieved higher CO conversion and selectivity to C5+ hydrocarbons. However, the Fischer-Tropsch synthesis catalyst achieved lower selectivity to methane and selectivity to CO2. In addition, the catalyst according to the present disclosure achieved selectivity to methane. This selectivity did not increase significantly due to the increase in temperature. This significantly solved the diffusion problem in the FT synthesis reaction.
[0243] Those skilled in the art should understand that the embodiments described herein are merely illustrative. Various substitutions, changes, and modifications can be made within the scope of the present disclosure. Therefore, the present disclosure is not limited to the above-described embodiments. However, the present disclosure is limited only by the claims. [Brief description of the drawings]
[0244] [Figure 1] 1 to 4 show SEM photographs of the raspberry-shaped oxide microspheres prepared in Preparation Examples 1 to 4. [Diagram 2]1 to 4 show SEM photographs of the raspberry-shaped oxide microspheres prepared in Preparation Examples 1 to 4. [Diagram 3] 1 to 4 show SEM photographs of the raspberry-shaped oxide microspheres prepared in Preparation Examples 1 to 4. [Figure 4] 1 to 4 show SEM photographs of the raspberry-shaped oxide microspheres prepared in Preparation Examples 1 to 4. [Diagram 5] FIG. 5 is a micrograph of the raspberry-shaped oxide microspheres prepared in Preparation Example 1. [Figure 6] FIG. 6 is a micrograph of the raspberry-shaped oxide microspheres prepared in Preparation Example 5. [Figure 7] FIG. 7 is a micrograph of the raspberry-shaped oxide microspheres prepared in Preparation Example 9. [Figure 8] FIG. 8 is a micrograph of the raspberry-shaped oxide microspheres prepared in Preparation Example 13. [Figure 9] FIG. 9 is a micrograph of the oxide microspheres prepared in Comparative Preparation Example 1. [Figure 10] FIG. 10 is a micrograph of the oxide microspheres prepared in Comparative Preparation Example 6. [Figure 11] FIG. 11 is a micrograph of the oxide microspheres prepared in Comparative Preparation Example 7. [Figure 12] FIG. 12 is a micrograph of the catalyst prepared in Procedure Example 1. [Figure 13] FIG. 13 is a micrograph of the catalyst prepared in Procedure Example 5. [Figure 14] FIG. 14 is a photomicrograph of the catalyst prepared in Comparative Example 1.
Claims
1. A raspberry-shaped oxide microsphere, which is a hollow microsphere having holes on its surface, the hollow microsphere has a hollow structure inside, the hole and the hollow structure are connected to form a cavity with an open end; the oxide in the raspberry-shaped oxide microspheres is one or more selected from the group consisting of alumina, silica, zirconia, magnesium oxide, calcium oxide and titania; The powder of raspberry-shaped oxide microspheres has a crushing rate of 0 to 1%.
2. The raspberry-shaped oxide microspheres according to claim 1, characterized in that the raspberry-shaped oxide microspheres have a particle size of 3-2500 μm, the hollow structure has a diameter of 1-2000 μm, the shell of the hollow microspheres has a thickness of 0.2-1000 μm, and the pores have a diameter of 0.2-1000 μm.
3. 2. The raspberry-shaped oxide microspheres according to claim 1, characterized in that said raspberry-shaped oxide microspheres have a sphericity of 0.50-0.
99.
4. A method for preparing raspberry-shaped oxide microspheres according to any one of claims 1 to 3, characterized in that it comprises the following steps: adding nitrates, peptizers, pore formers, the oxides and / or precursors thereof to the dispersant and stirring to obtain a dispersion slurry; Aging the dispersion slurry; and The aged dispersion slurry is sent to a drying device, and dried and shaped under conditions of an inlet gas temperature of 400-1200°C and an outlet gas temperature of 50-300°C to obtain raspberry-shaped oxide microspheres.
5. the nitrate is one or more selected from the group consisting of aluminum nitrate, zirconium nitrate, lanthanum nitrate, and yttrium nitrate; the peptizing agent is one or more selected from the group consisting of hydrochloric acid, sulfuric acid, nitric acid, formic acid, acetic acid, oxalic acid, sodium hydroxide, potassium hydroxide, barium hydroxide, calcium hydroxide, aluminum hydroxide, lithium hydroxide, magnesium hydroxide, zinc hydroxide, copper hydroxide, ferric hydroxide, lead hydroxide, cobalt hydroxide, chromium hydroxide, zirconium hydroxide, nickel hydroxide, ammonium hydroxide, anhydrous sodium carbonate, sodium carbonate monohydrate, sodium carbonate heptahydrate, sodium carbonate decahydrate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, amine compounds, alkali metal salts of alcohols, alkaloids, lithium alkyl metal compounds, hydrochlorides, sulfates, nitrates, formates, acetates, and oxalates; The pore former is one or more selected from the group consisting of starch, synthetic cellulose, polymeric alcohol and surfactant; The oxide and / or its precursor is one or more selected from the group consisting of an aluminum source, a silicon source, a zirconium source, and a titanium source, the aluminum source is one or more selected from the group consisting of pseudoboehmite, aluminum alkoxide, aluminum nitrate, aluminum sulfate, aluminum chloride, and sodium metaaluminate, the silicon source is one or more selected from the group consisting of silicate ester, sodium silicate, water glass, and silica sol, and the zirconium source is zirconium dioxide, zirconium tetrachloride, salt. zirconium oxide, zirconium hydroxide, zirconium sulfate, zirconium phosphate, zirconyl nitrate, zirconium nitrate, zirconium basic carbonate, and zirconium tetrabutoxide, the titanium source being one or more selected from the group consisting of titanium dioxide, metatitanic acid, titanium nitrate, titanyl sulfate, titanium dichloride, titanium trichloride, titanium tetrachloride, aluminum titanium chloride, tetraethyl titanate, tetrabutyl titanate, tetra-n-propyl titanate, and tetraisopropyl titanate; and 5. The method of claim 4, wherein the dispersant is one or more selected from the group consisting of water, an alcohol, a ketone, and an acid.
6. 5. The method of claim 4, wherein the mass ratio of the nitrate, the peptizer, the pore former, and the oxide and / or its precursor is (10-500):(1-10):(10-500):(10-1000).
7. 5. The method of claim 4, further comprising the step of adding a blasting agent to the dispersant, the blasting agent being one or more selected from the group consisting of picric acid, trinitrotoluene, nitroglycerin, nitrocellulose, Dana explosive, hexogen, and C4 plastic explosive, the blasting agent being added in an amount of 0-1% of the total dry weight of the nitrates, the peptizer, the pore former, and oxides and / or their precursors.
8. The method according to any one of claims 4 to 7, characterized in that the drying device is a flash drying device or a spray drying device.
9. The method according to any one of claims 4 to 7, characterized in that the aging is carried out at a temperature between 0 and 90°C.
10. FT synthesis catalyst comprising: a support; and an active metal component supported on the support, the active metal component being one or more selected from the group consisting of Co, Fe, and Ru; the support being the raspberry-shaped oxide microspheres according to any one of claims 1 to 3; and the oxide in the raspberry-shaped oxide microspheres being one or more selected from the group consisting of alumina and silica.
11. 11. The FT synthesis catalyst of claim 10, wherein the support is present in an amount of 25 to 95 wt. % on an oxide basis and the active metal component is present in an amount of 5 to 75 wt. % on an oxide basis, based on the weight of the catalyst.
12. The specific surface area of the carrier is 0.1 to 900 m 2 11. The FT synthesis catalyst according to claim 10, wherein the pore volume is 0.01 to 3.6 ml / g.
13. A method for preparing the FT synthesis catalyst according to any one of claims 10 to 12, comprising the steps of: providing raspberry-shaped oxide microspheres; calcining the raspberry-shaped oxide microspheres to obtain a support; and A step of impregnating the support with an impregnation solution of the compound containing the active metal component, drying and activating the support by calcination to obtain an FT synthesis catalyst.
14. 14. The method of claim 13, wherein the step of preparing the raspberry-shaped oxide microspheres comprises the steps of: adding a nitrate, a peptizer, a pore former, an aluminum source and / or a silicon source to the dispersant and stirring to obtain a dispersed slurry; Aging the dispersion slurry; The aged dispersion slurry is sent to a drying device, and dried and shaped under conditions of an inlet gas temperature of 400-1200°C and an outlet gas temperature of 50-300°C to obtain raspberry-shaped oxide microspheres.
15. The nitrate is one or more selected from the group consisting of aluminum nitrate, zirconium nitrate, lanthanum nitrate and yttrium nitrate; the peptizing agent is one or more selected from the group consisting of hydrochloric acid, sulfuric acid, nitric acid, formic acid, acetic acid, oxalic acid, sodium hydroxide, potassium hydroxide, barium hydroxide, calcium hydroxide, aluminum hydroxide, lithium hydroxide, magnesium hydroxide, zinc hydroxide, copper hydroxide, ferric hydroxide, lead hydroxide, cobalt hydroxide, chromium hydroxide, zirconium hydroxide, nickel hydroxide, ammonium hydroxide, anhydrous sodium carbonate, sodium carbonate monohydrate, sodium carbonate heptahydrate, sodium carbonate decahydrate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, amine compounds, alkali metal salts of alcohols, alkaloids, lithium alkyl metal compounds, hydrochlorides, sulfates, nitrates, formates, acetates, and oxalates; The pore former is one or more selected from the group consisting of starch, synthetic cellulose, polymeric alcohol and surfactant; The aluminum source is one or more selected from the group consisting of pseudoboehmite, aluminum alkoxide, aluminum nitrate, aluminum sulfate, aluminum chloride, and sodium metaaluminate; The silicon source is one or more selected from the group consisting of silicate ester, sodium silicate, water glass and silica sol; 15. The method of claim 14, wherein the dispersant is one or more selected from the group consisting of water, an alcohol, a ketone, and an acid.
16. 15. The method of claim 14, wherein the mass ratio of the nitrate, the peptizer, the pore former, and the aluminum source and / or the silicon source is (10-500):(1-10):(10-500):(10-1000).
17. 15. The method of claim 14, further comprising the step of adding a blasting agent to the dispersant, the blasting agent being one or more selected from the group consisting of picric acid, trinitrotoluene, nitroglycerin, nitrocellulose, Dana explosive, hexogen, and C4 plastic explosive, the blasting agent being added in an amount of 0-1% of the total dry weight of the nitrate, the peptizer, the pore former, and the aluminum source and / or silicon source.
18. 15. The method of claim 14, wherein the drying device is a flash dryer or a spray dryer.
19. 15. The method according to claim 14, wherein the aging is performed at a temperature of 0-90°C, the firing is performed at a temperature of 400-1300°C, the drying is performed at a temperature of 80-200°C, and the activation by firing is performed at a temperature of 200-800°C.
20. Use of the FT synthesis catalyst according to any one of claims 10 to 12 in an FT synthesis reaction.
Citation Information
Patent Citations
Single-hole silicon dioxide hollow microsphere and preparation method thereof
CN102249245A
Hollow microspheric Fischer-Tropsch synthesis catalyst and preparation and application
CN108144613A
Apple-shaped hollow molecular sieve microspheres and preparation method and application thereof
CN108404970A
Tsubogatashokubaioshosurutankasuisofuiidonosuisokashori
JP1976106102A
Method of producing catalyst carrier
JP1979019485A